2013
DOI: 10.1093/rheumatology/ket131
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between interleukin-6 and cardiac involvement in systemic sclerosis

Abstract: IL-6 level is increased in patients with SSc and significantly correlates with LV diastolic dysfunction, NT-proBNP and EUSTAR score. These results support the role of IL-6 in the development of cardiac disease in SSc patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 16 publications
1
15
2
Order By: Relevance
“…Recently, Jurisic et al . reported that IL-6 levels are increased in patients with SSc and correlate with LV diastolic dysfunction [36]. More studies are needed investigating the relationship of other biomarkers with diastolic dysfunction in patients with SSc.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Jurisic et al . reported that IL-6 levels are increased in patients with SSc and correlate with LV diastolic dysfunction [36]. More studies are needed investigating the relationship of other biomarkers with diastolic dysfunction in patients with SSc.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma IL-6 level was found to be higher in ATA-positive and anti-RNAP III-positive patients but not in ACA-positive SSc patients [ 60 ]. In one study, serum IL-6 was shown to correlate with disease activity [ 61 ], although this was not found by others [ 62 ]. In a genetic association study, IL-6 polymorphism in SSc patients was shown to be associated with disease activity and HAQ-DI, unfortunately circulating IL-6 was not measured [ 63 ].…”
Section: Biomarkers For Disease Activitymentioning
confidence: 92%
“…The complex of IL-6-soluble IL-6R,andIL-6-anti-IL-6autoantibodycanbindtogp130and induce signal transduction in SSc (68,69). Significant correlationshavebeenobservedbetweenserumlevelsofIL-6 andtheseverityofskinthickening(70),diseaseprogression ininterstitiallungdisease(63),andcardiacinvolvement (64,65);thesecomplicationsofSScarecharacterizedbytissuefibrosis.InadditiontoelevatedcirculatingIL-6levels,cultured fibroblastsfromSScpatientswerefoundtoexpressstrikingly high levels of IL-6 at both the transcriptional and the proteinlevels (71)(72)(73)(74).InhibitionofIL-6signaltransductionusing ananti-IL-6antibodyattenuatedcollagenproductionincul-turedfibroblastsofSScpatients (14). Additionally,elevated secretion of IL-6 from peripheral monocytes was observed inpatientswithSSc-associatedinterstitiallungdisease(75).…”
Section: Elevation Of Il-6 In Sscmentioning
confidence: 99%
“…Insummary,highconcentrationsofIL-6arefoundinthe seraofSScpatients (10)(11)(12)(13)15,(63)(64)(65)andhavebeenshown tobehighlycorrelatedwiththeseverityoftissuefibrosis.In vitroexperimentsfurthersupporttheseobservations,demonstratinganincreasedsecretionofIL-6byculturedskinfi-broblasts,monocytes,andBlymphocytesfrompatientswith SSc (71)(72)(73)(74)(75)(76).Inparticular,theoverproductionofIL-6canlead to excessive collagen production by fibroblasts, which contributestotissuefibrosisinSSc (11,13,14) (Fig.2).…”
Section: Elevation Of Il-6 In Sscmentioning
confidence: 99%